Real Time Fishpond Monitoring to Optimize a Nursery Freshwater with Distribution Database - Agung Kridoyono; Mochamad Sidqon (JEECS (Journal of Electrical Engineering and Computer Sciences), 2018)
The aim of my research is to optimize a nursery freshwater by fishpond monitoring that can be displayed on desktopbase so the behavior of fish with fishpond condition can be observed how suitable fish against fishpond where anursery is affected by the place , the media and the condition. The data were drawn on monitoring is temperatureand humidity by more than one sensor taken using one microprocessor. Using temperature sensor to get datacondition in fishpond, data from fishpond is processed by microcontroller as an input and sent to desktop to displaythen distributed on database for data record in real time asynchronous serial communication between PC andmicrocontroller. Getting ideal condition is the goal of this device, because real time data communication ifsomething wrong or not suitable on media, the fishpond condition can be handled directly by fitting the volume offish or the condition of water. 28-300C is ideal temperature condition for seedling that influence the appetite of thefish. By using realtime database distribution methodology, The influence of fish quantity and nursery media can beobserved and fish behavioral can be recorded every season.